Educating investors about dividends - Andreas Hackethal; Tobin Hanspal; Samuel M. Hartzmark; Konstantin Bräuer (Goethe University Frankfurt, Center for Financial Studies (CFS), 2024)
We educate investors about the benefits of dividend reinvestment and costs of misperceiving dividends as free income. The intervention increases planned dividend reinvestment in survey responses. Using trading records, we observe a causal increase in dividend reinvestment in the field of roughly 50 cents for every euro received. This holds relative to investors' prior behavior and various control samples. Investors who learned the most from the intervention update their trading the most. The results suggest the free dividends fallacy is a significant source of dividend demand. Our study demonstrates that simple, targeted, and focused educational interventions can affect investment behavior.
Keywords: 330